EXAMINING RATER PERCEPTION OF HOLDS AS A VISUAL CUE OF LISTENER NONUNDERSTANDING. Issue 5 (14th December 2022) - McDonough, Kim; Lindberg, Rachael; Trofimovich, Pavel
Abstract: This study examined whether university students perceive holds (i.e., a listener's temporary cessation of dynamic movement) as a visual cue of nonunderstanding. Conversations between English second language (L2) university students were sampled to extract episodes of other-initiated repair through open clarification requests (e.g., what?, sorry? ). Brief, silent video clips were presented to 60 raters across two experiments who assessed the listener's comprehension, which was their perception about how well the listener had understood the speaker. Experiment 1 tested whether raters can differentiate between the onset and release of listener holds while Experiment 2 examined whether they are sensitive to the sequential organization of holds. Results indicated that raters clearly differentiated between hold onsets and releases and were sensitive to the temporal position of holds in the entire repair sequence. Taken together, these findings suggest that holds are a reliable signal of nonunderstanding with potential implications for L2 teaching and assessment.